Systematic review of the oxy-hemodynamic effects of bath in hospitalized critical adults - Dalmo Valério Machado de Lima; Rubia Aparecida Lacerda (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <w:LsdException